Communication, Power and Resistance in the Arab Spring: Voices of Social Change from the South. (July 2013) - Dutta, Mohan
This article articulates the processes of resistance that were constituted in participation of the youth in online and offline spaces in the Arab Spring. Through an online ethnography of the various sites of resistance, the article foregrounds the complementary roles played by communication spaces, the broader economic context of neoliberal policies and the ways in which resistance offered entry points for alternative imaginations. The theoretical discussion in the article puts forth the argument that the struggle for voice rooted in the politics of the global South is also a struggle for economic opportunity, economic decision-making and economic participation, working with culturally-rooted expressions that find global presence through interlinkages of resistance in regional-global networks.